Changes in Cerebral Oxidative Metabolism during Neonatal Seizures Following Hypoxic–Ischemic Brain Injury - Mitra, Subhabrata; Bale, Gemma; Mathieson, Sean; Uria-Avellanal, Cristina; Meek, Judith; Tachtsidis, Ilias; Robertson, Nicola J. (Frontiers in Pediatrics, 2016)
Seizures are common following hypoxic ischemic brain injury in newborn infants. Prolonged or recurrent seizures have been shown to exacerbate neuronal damage in the developing brain, however the precise mechanism is not fully understood. Cytochrome-c-oxidase is responsible for more than 90% of ATP production inside mitochondria. Using a novel broadband near-infrared spectroscopy system we measured the concentration changes in the oxidation state of cerebral cytochrome-c-oxidase (Δ[oxCCO]) and hemodynamics during recurrent neonatal seizures following hypoxic ischemic encephalopathy in a newborn infant. A rapid increase in Δ[oxCCO] was noted at the onset of seizures along with a rise in the baseline of amplitude integrated electro-encephalogram (aEEG). Cerebral oxygenation and cerebral blood volume fell just prior to the seizure onset but recovered rapidly during seizures. Δ[oxCCO] during seizures correlated with changes in mean EEG voltage indicating an increase in neuronal activation and energy demand. The progressive decline in the Δ[oxCCO] baseline during seizures suggests a progressive decrease of mitochondrial oxidative metabolism.